“孔顏之樂”、壽命與生命之道: The Confucian View of Happiness, Longevity and Way of Life - LU, Feng (International Journal of Chinese & Comparative Philosophy of Medicine, 2014)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Professor He Huaihong observes that the lives of famous Chinese philosophers in the 20th century were longer than those of their French counterparts and attributes this phenomenon to differences in these individuals’ ways of life and guiding philosophies. I broadly agree with Professor He. However, I make a different claim for the fundamental difference between Chinese philosophy and Western philosophy. According to Chinese philosophy, human beings’ supreme goal lies within human life, whereas that defined by Western philosophy isexternal to human life. According to modern definitions, humanity’s ultimate aim is to construct paradise on Earth through scientific and technological innovation and economic growth. The corollaries of this modern goal are that no single individual can ever be satisfied with her/his situation and that society as a whole can never be satisfied by the level of its economy. In short, modernity legitimizes global greed. As a result, many elites in modern society are greedy. However, greedy people cannot also be happy and unhappiness has been statistically linked with unhealthiness. Before the 20th century, most of China’s philosophers were absolutely virtuous and capable of remaining peaceful in any situations, and thus usually enjoyed long lives. DOWNLOAD HISTORY | This article has been downloaded 81 times in Digital Commons before migrating into this platform.